Heme pathway evolution in kinetoplastid protists - Cenci, Ugo; Moog, Daniel; Curtis, Bruce A; Tanifuji, Goro; Eme, Laura; Lukeš, Julius; Archibald, John M (BMC evolutionary biology, 2016)
BACKGROUND: Kinetoplastea is a diverse protist lineage composed of several of the most successful parasites on Earth, organisms whose metabolisms have coevolved with those of the organisms they infect. Parasitic kinetoplastids have emerged from free-living, non-pathogenic ancestors on multiple occasions during the evolutionary history of the group. Interestingly, in both parasitic and free-living kinetoplastids, the heme pathway-a core metabolic pathway in a wide range of organisms-is incomplete or entirely absent. Indeed, Kinetoplastea investigated thus far seem to bypass the need for heme biosynthesis by acquiring heme or intermediate metabolites directly from their environment. RESULTS: Here we report the existence of a near-complete heme biosynthetic pathway in Perkinsela spp., kinetoplastids that live as obligate endosymbionts inside amoebozoans belonging to the genus Paramoeba/Neoparamoeba. We also use phylogenetic analysis to infer the evolution of the heme pathway in Kinetoplastea. CONCLUSION: We show that Perkinsela spp. is a deep-branching kinetoplastid lineage, and that lateral gene transfer has played a role in the evolution of heme biosynthesis in Perkinsela spp. and other Kinetoplastea. We also discuss the significance of the presence of seven of eight heme pathway genes in the Perkinsela genome as it relates to its endosymbiotic relationship with Paramoeba.
Keywords: symbióza; Lateral gene transfer; hem; Prokinetoplastina; přenos genů horizontální; fylogeneze; Phylogeny; Eukaryota; Kinetoplastida; Endosymbiosis; biologická evoluce; Gene Transfer, Horizontal; Animals; Biological Evolution; zvířata; Perkinsela; Paramoeba pemaquidensis; Evolution; Heme; Symbiosis; Kinetoplastea